The Paradox of Machiavellianism: Machiavellianism May Make for Productive Sales but Poor Management Reviews - Ricks, James (Journal of business ethics, 1999)
This article investigates the effects of Machiavellianism (MACH) on sales performance. Results indicate that those who possess high Machiavellian traits are more productive but received lower overall managerial ratings. Findings suggest that Machiavellianism may in certain circumstances, be somewhat advantageous for long-term sales performance.